2021
DOI: 10.1111/cea.13820
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous factors in the pathogenesis of atopic dermatitis: Irritants and cutaneous infections

Abstract: Atopic dermatitis (AD) is a chronic relapsing inflammatory cutaneous disease that is often associated with other atopic symptoms, such as food allergy, allergic rhinitis and asthma, leading to significant morbidity and healthcare costs. The pathogenesis of AD is complicated and multifactorial. Although the aetiology of AD remains incompletely understood, recent studies have provided further insight into AD pathophysiology, demonstrating that the interaction among genetic predisposition, immune dysfunction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 127 publications
(242 reference statements)
0
9
0
Order By: Relevance
“…Studies also revealed that VitD promotes human cathelicidin generation, which has been considered insufficient in AD [ 10 , 13 ] and improves innate immunity. Given that the mechanism of development of AD relates to skin barrier dysfunction and immune response dysregulation [ 14 , 15 ], VitD might be related thereto. Epidemiological studies have also shown evidence with regard to VitD and the development of atopic eczema [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also revealed that VitD promotes human cathelicidin generation, which has been considered insufficient in AD [ 10 , 13 ] and improves innate immunity. Given that the mechanism of development of AD relates to skin barrier dysfunction and immune response dysregulation [ 14 , 15 ], VitD might be related thereto. Epidemiological studies have also shown evidence with regard to VitD and the development of atopic eczema [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors supported by strong epidemiological data are: living in an urban area associated with specific hygiene-related exposures, increased stress, and higher exposure to traffic-related air pollution, including particulate matter, sulfur, carbon, nitrogen, and benzene components connected with urbanization and industrialization [ 90 , 91 , 92 ]. Specific external irritants, such as alkaline soaps, detergents microplastics, nanoparticles, and hard water have also been reported to play important roles in the development and aggravation of atopic eczema [ 93 , 94 ]. There is some evidence for the effects of maternal or postnatal tobacco exposure, long-term exclusive breastfeeding, routine childhood vaccinations, viral or bacterial infections, and farm environments; however, epidemiological data are still inconsistent [ 89 , 90 , 91 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Der p1 plays as a major allergen and has a proteinase activity (as an irritant) on AECs (inducing intracellular oxidative stress and impairing epithelial barrier). 16,24 The release of CC16 from Clara cells was increased after acute exposure to environmental factors (smoke and allergens) but decreased in chronic exposure condition with progressive damage of AECs. [25][26][27] The present study assessed CC16 production from AECs in response to Der p1 in a time-dependent manner.…”
Section: Effects Of Der P1 On the Production Of Cc16 And Cytokines Fr...mentioning
confidence: 99%